Problem-based Learning in Basic Physics—IX - Mody, A.K.; Pradhan, H. C. (SCHOOL SCIENCE, 2015)
In this article, ninth in the Problem-based Learning (PbL) series, we consider various examples from different areas of physics where we often make approximations. We are trying to discuss the meanings of these approximations.